Adolescent health experience after abortion or delivery (AHEAD) trial: formative protocol for intervention development to prevent rapid, repeat pregnancy. Issue 1 (December 2015) - Hindin, Michelle; Rodriguez, Maria; Gonsalves, Lianne; Say, Lale
Abstract Background There is a high unmet need for modern contraception among adolescents, and adolescent girls who have already been pregnant are especially vulnerable to a rapid, repeat pregnancy (defined as a subsequent pregnancy within two years). The Adolescent Health Experience after Abortion or Delivery (AHEAD) trial will design, pilot, finalize, and ultimately evaluate an intervention targeted at reducing rapid repeat pregnancy. This protocol presents the methods for the first phase–formative research to identify key determinants of contraceptive use and rapid, repeat unintended pregnancy among adolescents. Methods/design The determinants of adolescent pregnancy are known to vary by context; therefore, a dissimilar set of three countries will be selected to enable evaluation of the intervention in diverse cultural, political and economic environment, and to allow the intervention to be tested with a fuller range of ever-pregnant adolescents, including those who have chosen to terminate their pregnancy as well as those who are mothers. We will also consider marital status in settings where it is common for adolescents to marry. Focus group discussions (FGDs) will be conducted to examine barriers and facilitators to using contraception; preferred methods of overcoming these barriers; and perceptions of the services and information received. Key informant (KI) interviews will take place with various cadres of healthcare providers, health and education officials, and members of key youth and health organizations that work with adolescents. These interviews will focus on perceptions of pregnant adolescents; perceived information, skills, and motivations required for adolescent uptake of contraception; and experiences, challenges, and attitudes encountered during interactions. Discussion The findings from this first formative phase will be used to develop an intervention for preventing rapid, repeat unintended pregnancy among adolescents. This intervention will be piloted in a second phase of the AHEAD trial.